433 Is miR let-7c protective against Acute Chest Syndrome in Sickle Cell Disease?. (April 2022) - Fan, James; Gemel, Joanna; Lang, Theodore; Beyer, Eric; Lapping-Carr, Gabrielle
Abstract : OBJECTIVES/GOALS: We have shown that small extracellular vesicles (exosomes) isolated from patients with a history of ACS disrupt the endothelium in vitro. Sequencing of miRNA contents of these vesicles suggested that miR let-7c was differentially expressed. The current study was designed to determine the relationship between miR let-7c levels and ACS. METHODS/STUDY POPULATION: We identified 16 subjects from the SCD Lungomics biobank at the University of Chicago Comer and La Rabida Childrens Hospitals who had samples obtained at baseline. Among them, 9 had a history of ACS (ACS(+)) and 7 did not (ACS(-)). For all subjects, we reviewed clinical data relevant to their SCD and laboratory data (including hemoglobin, absolute reticulocyte count, white blood cell count) obtained at the same time as the baseline samples. RNA was isolated from the plasma and miR let7c was quantified using quantitative RT-PCR. RESULTS/ANTICIPATED RESULTS: Subjects were similar clinically, except that those with a history of ACS were more likely to be on hydroxyurea (p<0.05) and to have obstructive sleep apnea (p<0.05). Hematologic laboratory values were similar irrespective of ACS history. The mean miR let-7c level was 2-fold less in subjects with a history of ACS than in those who had never had ACS (p<0.05). A plasma miR let-7c level < 1 (normalized to the control subjects) had a positive predictive value of 0.78 for history of ACS and a sensitivity of 78% and specificity of 71%. Among subjects with a history of ACS, the let7c levels did not correlate with time since the last ACS event. However, among subjects who developed ACS following the baseline samples, higher miR let-7c levels correlated with increased length of time to next ACS event (R=0.8). DISCUSSION/SIGNIFICANCE: Our results in a group of subjects with SCD show that plasma miR let-7c levels are decreased in subjects with a history of ACS. They suggest that miR let-7c may be protective against development of ACS and that measurement of its levels could be a useful biomarker to assess or predict risk for this complication of SCD.